Liposarcoma of the Thyroid. (2004) - Mitra, A.; Fisher, C.; Rhys-Evans, P.; Harmer, C.
Abstract : Liposarcoma of the thyroid gland is rare with only 3 cases reported in the English literature. We present a further two patients whom we have recently treated: a 49 year old lady with a myxoid liposarcoma and a 71 year old man with a pleomorphic liposarcoma. Both underwent macroscopic excision of tumour but had positive margins, so were then treated with external beam radiotherapy. The former patient died from metastases 10 months after presentation, the latter remains alive but has developed metastatic disease on follow up at 24 months. We recommend the use of high dose radiotherapy following radical surgery as margins of excision are usually narrow in this most difficult region. The role of chemotherapy is yet to be established.